Module Principle of Organization of Extracurriculum Activities of Students - Bereka, Victor (Pedagogical Discourse, 2012)
The problem of module principle of organization of extracurriculum activities of students from the point of view of providing the improving of effectiveness of educational process at the higher educational establishment has been studied. Expediency of module principle use in the process of individual educational activity has been proved